Balanced scorecards & operational dashboards with Microsoft Excel - Person, Ron, 1948- (Indianapolis, IN : John Wiley & Sons, Inc., 2013)
Learn to maintain and update scorecards and dashboards with Excel Balanced Scorecards and operational dashboards measure organizational performance and Microsoft Excel is the tool used worldwide to create these scorecards and dashboards. This book covers time-proven step-by-step processes on how to guide executive teams and managers in creating scorecards and dashboards. It then shows Excel developers how to create those scorecards and dashboards. This is the only book that converts theory into practice. The author addresses the people and processes you need to identify strategy ...
"Balanced Scorecards and operational dashboards measure organizational performance and Microsoft Excel is the tool used worldwide to create these scorecards and dashboards. This book covers time-proven step-by-step processes on how to guide executive teams and managers in creating scorecards and dashboards. It then shows Excel developers how to create those scorecards and dashboards. This is the only book that converts theory into practice. The author addresses the people and processes you need to identify strategy and operational metrics and then implement them in dashboards in three versions of Excel. You'll learn how balanced scorecards help organizations translate strategy into action and the ways that performance dashboards enable managers monitor operations."--Publisher's description.
Introduction -- Part I. Strategic performance with balanced scorecards. Accelerating strategic performance -- Developing your strategic foundation -- Preparing to build your balanced scorecard -- Step-by-step to building your strategy map -- Step-by-step from strategy to action -- Step-by-step to selecting metrics and setting targets -- Step-by-step to developing your implementation plan -- Step-by-step to rollout and strategic reviews -- Part II. Operational performance with dashboards. Developing executive and operational dashboards -- Mapping your operational processes -- Identifying critical metrics and key performance indicators -- Part III. Building maps, scorecards, and dashboards. Creating dashboards for decision-making -- Drawing process and strategy maps -- Using Microsoft Excel for balanced scorecards and dashboards -- Text-based dashboards -- Custom labels and formatting -- Working with data that changes size -- Retrieving data from lists and tables of data -- Creating miniature charts and tables -- Controlling charts with menus, combo boxes, and buttons -- Working with pivot tables -- Working with power pivot -- Smoothing data and forecasting trends -- Identifying targets and displaying alerts -- Building powerful decision-making charts -- Drilling to detail -- Using Excel add-ins for extra capabilities -- Finishing touches -- Data integration methods -- Publishing balanced scorecards and dashboards.
Description based on resource, viewed November 11, 2021.
John Wiley and Sons
Keywords: Microsoft Excel (Computer file); Microsoft Excel (Computer file); Balanced scorecard (Management); Performance technology; Dashboards (Management information systems); Tableaux de bord (Gestion); COMPUTERS -- Management Information Systems; Balanced scorecard (Management); Dashboards (Management information systems); Performance technology